Filantropi Islam Masjid Baitul Huda Untuk Pemberdayaan Sosial - Wanda Aulia, Nurul; Nurlaela, Neng Deva (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2026)
The Baitul Huda Mosque, which had been quiet since its establishment in 2022 on the side of a main road, needed revitalization to become a center worship and social activities; thus, the “makan-makan” philanthropy program was designed as a transit mosque to attract congregants through free lunch after the Dhuhr prayer, fostering brotherhood, and strengthening the habit of congregational prayer .The primary objectives include providing for spiritual and food needs, empowering the community, and developing a holistic mosque ecosystem based on Islamic philanthropy Management approaches include collaborative charity contributions via social media, integration of spiritual rituals (dhikr, brief study sessions), and tiered programs: daily (varied meals), weekly (study sessions, Quran recitation improvement, elderly care), monthly (rice/vegetable distribution, iftar), and support for other mosques/Islamic boarding schools The findings indicate a significant increase in congregants, the fulfillment of the needs of the poor and the elderly, strong social solidarity, and inclusive spiritual well-being. This comprehensive program establishes the mosque as a self reliant and sustainable center of Islamic civilization.